1998
DOI: 10.1002/(sici)1097-0231(19981130)12:22<1673::aid-rcm385>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the internal energy distributions of ions produced by different electrospray sources

Abstract: The internal energies of the emitted ions can be modulated in an electrospray source through different experimental conditions. However, the fragmentation pattern depends also on conditions that cannot be controlled by the operator, e.g. the geometry of the source or the mode of transfer of the ions. These differences make difficult the comparison of the electrospray mass spectra obtained with different mass spectrometers. A method for the calibration of the internal energies of ions produced by an electrospra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
195
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(211 citation statements)
references
References 7 publications
(8 reference statements)
12
195
2
Order By: Relevance
“…The similarity index in this range is better than 0.99, comparable to that observed among the quadrupole type instruments. This collision energy range corresponds to the beginning of fragmentation; the survival yield [10,11,14] is 50% or higher (i.e., the sum of fragment ion intensities is less than the intensity of the protonated molecule). This energy range may be useful for identifying low energy fragments (e.g., for identifying glycoforms).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity index in this range is better than 0.99, comparable to that observed among the quadrupole type instruments. This collision energy range corresponds to the beginning of fragmentation; the survival yield [10,11,14] is 50% or higher (i.e., the sum of fragment ion intensities is less than the intensity of the protonated molecule). This energy range may be useful for identifying low energy fragments (e.g., for identifying glycoforms).…”
Section: Resultsmentioning
confidence: 99%
“…Note that if one peak was missing in one of the spectra, it was considered to be equal to the cutoff value (1%). Note, Equations (1-3) have been used before (Refs [14][15][16][17][18]). Here we adopt them for our purpose.…”
Section: Spectral Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the effect of various instrumental parameters on the energetics of the ESI source have also been conducted, and they aimed at gaining a better understanding of the ionization mechanism and of the possibility of efficiently tuning the internal energy of the ions generated [49,[52][53][54]. It has been demonstrated that in ESI the shape of the P(E) curve corresponds approximately to a thermal energy distribution [53].…”
Section: Esorption Electrospray Ionization (Desi) Is An Ambient Ionmentioning
confidence: 99%
“…These observations are in keeping with the suggestion that initially an ion's kinetic energy is quenched through collisions with the helium buffer gas and that much of this quenched kinetic energy is redistributed as internal energy within the ion, thus the internal energy of the ion rises initially [11].°Quenching°of°the°internal°energy°(mainly°vibra-tional) is much less efficient and therefore occurs over longer°time-scales°(a°factor°of°ϳ10 2°l onger)° [11].°How- ever, these time-scales for the collisional cooling of ion internal energy do not agree with those observed by Danell°and°Glish° [1],°who°observed°that°the°boundary activated decomposition onsets of leucine-enkephalin ions formed by nanoflow electrospray did not vary with the collisional cooling period prior to dissociation, and therefore concluded that the ions are collisionally cooled within a few milliseconds. This apparent discrepancy in collisional cooling time-scales is likely to be attributable in part to the different ionization techniques used (resulting in ion populations of different internal and kinetic energies as discussed above), and partly because of the different instruments used (source geometry and transfer lens voltages have both been shown°to°effect°internal°energy° [19]). °It°is°also°possible that the discrepancy may be due in part to the different techniques used to gauge internal energy.…”
Section: Effect Of Ion "Cool Times" On Internal Energymentioning
confidence: 99%